Detection of Tetracycline, Doxycycline, Chlortetracycline, and Oxytetracycline Antibiotics in Nineveha Drug Wastewater - Ibraheem, Jathwa A.; Abdul-Ahad, Muna Yousif (Nahrain University College of Engineering Journal, 2012)
This paper describes a simultaneous method for the determination of tetracycline (TC), and tetracycline’s derivatives; doxycycline (doxysam), chlortetracycline (chlor-TC), and oxytetracycline (oxy-TC), in Nineveh Drug Factory (NDF) antibiotic industrial water course effluent, using solid-phase extraction followed by liquid chromatography separation. The identification of the target antibiotics in environmental samples was based on comparison of their HPLC peaks with those of the corresponding reference standard solutions. It was found that compromisingly satisfactory separation of the investigated antibiotics and stable base line could be achieved by using acetonitrile–formic acid solution as a binary mobile phase system. Still the compounds were separated on a Sep-Pak C18 cartridge with a resolve CN guard column using gradient elution and UV wavelength of 280 nm. The reported data indicated that tetracycline is the most frequently detected antibiotic in the samples. It was detected in five out of eight effluent water samples, with the maximum concentration of 0.412 ?g/l. Doxycycline were detected in four with a maximum of 0.349 ?g/l, chlortetracycline was found in only one sample (0.358 ?g/l), while oxytetracycline was not detected.